The Implementation of Child-Friendly Education During the Covid-19 Pandemic in Madrasah Aliyah Negeri Bandar Lampung - Sri Ilham Nasution; M Saifuddin (AT-TA'LIM, 2022)
Abstract: Long periods of online learning as a result of a pandemic with no apparent end date can result in a variety of compensatory behaviors, one of which is performing acts of aggression or unpleasant deeds towards children (students). Action violence and deeds that are harmful to children can happen at any time, by anybody, and anywhere, including in the classroom by instructors during the Covid-19 pandemic. As a result, child-friendly education in schools must be introduced. The goal of this study is to describe how child-friendly education was used at Madrasah Aliyah NegeriÂ  Bandar Lampung during the Covid-19 outbreak. Teachers and students are used as respondents in the study, which employs qualitative approaches. Madrasah Aliyah NegeriÂ  Bandar Lampung implemented child-friendly education during the Covid outbreak by following emergency curriculum requirements and adhering to instructor restrictions when conducting online learning. The provision of learning conditions that are clean, beautiful, friendly, beautiful, inclusive, healthy, safe, and comfortable as reflected in the components: 1) policies, 2) curriculum implementation, 3) trained educators and education personnel, 4) child-friendly facilities and infrastructure, 5) participation of children, 6) participation of parents, community, alumni, business world, community in child-friendly education.